A South African perspective on the 2023 IPBES Thematic Assessment Report on Invasive Alien Species and their control - Wilson, John R.U.; Faulkner, K.T.; Fernández Winzer, L.; McCulloch-Jones, E.J.; van Wilgen, B.W.; Blanchard, R.; Carbutt, C.; Dechoum, M.S.; Foxcroft, L.C.; Greve, M.; Hui, C.; Ivey, P.; et al. (African Biodiversity & Conservation, 2026)
Background: Biological invasions are a major threat to biodiversity and sustainable development. A global assessment of biological invasions released in 2023 by the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES), concluded that while invasions ‘…cause dramatic and, in some cases, irreversible changes…’ they can be ‘…overcome through a context-specific integrated governance approach’.Aim: Here we evaluate insights from the IPBES assessment in the context of South Africa and explore how these insights could inform the development of a national policy and strategy to address biological invasions.Results: Trends and status of biological invasions in South Africa are similar to those seen globally, but there are some distinct local nuances. South Africa has: 1) a long history of invasions with negative impacts caused especially by invasive trees and freshwater fishes, whilst invasive marine invertebrates have transformed large parts of the coastline; 2) a long history of control (biological control was first implemented in 1913) with large-scale, state-run invasive species management programmes currently in place; 3) a comprehensive regulatory system (e.g., there is provision for beneficial invasive species to be used under permits); 4) relatively high levels of awareness and engagement (at least among some stakeholder groups); and 5) a well-connected community of practice.Discussion: Efforts to limit introductions (intentional or unintentional) are difficult given South Africa’s extensive and porous borders and the pressing need to increase trade and travel. Regulatory and implementation efforts aimed at prevention are improving, with the newly established Border Management Authority aiming to integrate biosecurity interventions at ports of entry. Such integrated governance is, we argue, needed more broadly if affected sectors, society groups and stakeholders are to be effectively included in decision-making and management. A more systematic flow of information from observation to action is essential, as is better feedback between research, policy and implementation at all scales. Biological invasions will continue to pose threats, but many of these can be effectively mitigated through focussed interventions. Co-ordinating such interventions in the context of other cross-cutting global change challenges and initiatives is a cost-effective way of protecting and improving livelihoods, human health, quality of life and biodiversity.